The Effect of Leadership Style and Welfare on The Performance of Manado Religious and Education Training Center - Rusli; Wibowo; Burhanuddin Tola (Program Studi S3 Ilmu Manajemen, 2019)
The aim of this study is to observe and analyze the influence of Leadership Styles and Welfare on the Performance of Employees in Manado Religious Education and Training Center. This study used Partial Last Square (PLS) method. The population of this study was 60 employees (N = 60), and all of these employees were sampled (n = 60) with an error rate of 5% (0.05). Data was collected based on questionnaire with Likert scale. The results of this study showed that there are direct contributions between Leadership style and welfare variables on employee performance. Overall, Leadership style and Welfare have a positive and very strong influence on Employee Performance.These results showed the importance of improving the quality of Leadership Styles and Welfare to improve the Performance of Employees in Manado Religious Education and Training Center.